Synthesis of carbon-opacified-silica-aerogel using bamboo leaf - Kien, W.K; Yusoff, Rozita; Abdul Raman, Abdul Aziz; Abdullah, E.C. (2013)
Opacification of silica aerogel to reduce its thermal conductivity had received much attention in recent years. In such context, aerogels are normally opacified with carbon black to mask out the radiative heat loss in the infrared region. The motivation of this work is to use bamboo leaf as a single source to synthesize water glass and activated carbon. Both of these prec~rsors ,:ere then used. to synthesize and opacify silica aerogel. Since bamboo leaf is an agriculture waste, this provides an alternatIve lost cost source to synthesize carbon-opacified-silica-aerogel.The properties of bambo.o leaf .aerogel that opacified activated carbon was compared then with other aerogels including those opacified With carbon black and also aerogel synthesized from TEaS alkoxide.Results show that aerogels opa~ified with activated carbon synthesized has bulk density of 0.069±0.0014 g.cm", porosity of 97.9%, .B.ET specific surface area ~f 3_~0.5±3.7m2.g-l, total pore volume of 1.38±0.07cm3.g -I and thermal conductivity of 0.0311±0.009W.m .K . TGA of aerogels also show that opacified aerogel is thermally stable up to 495°C and therefore suitable to be used in thermal insulation at high temperature.